Arteterapia a través del teatro para el desarrollo de la expresión oral y corporal de los estudiantes con necesidades educativas especiales, asociados a dificultades de aprendizaje, de la UE “Cap. Giovanni Calles Lascano” de comunidad Jatari campesino, cantón Riobamba, parroquia Calpi, período 2021-2022 - Pérez Logroño, Tania Maritza (2022)
ABSTRACT: The subsequent investigation arises from the problem found in the academic unit Captain Giovanni Calles Lascano, which is summarized in a low development of oral and body language of students with special educational needs before which the objective of creating and applying theater-based art therapy guide for developing the verbal and corporal expression of students with special educational needs, to specify it, the theoretical basis is established in chapter two, through scientific and academic research; The methodological approach to which this work responds is quantitative, with a pre-experimental design, through a field and longitudinal typology with an application level, maintaining a deductive method; which allowed us to propose two data collection instruments, the first an observation sheet that evaluates the students and a survey that will enable obtaining the level of knowledge of teachers about art therapy, these instruments were validated by three experts in the study areas which allowed to give the respective reliability and validity to them. After this process, individual conclusions and recommendations were made, from which it can be summarized that the use of puppets benefits elementary school children. At the same time, shadow theater is ideal for middle and high school students. Dramatization is an excellent theatrical technique for the upper basic; in favor of improving and strengthening the development of oral and corporal expression